Cali, Colombia : Toward a City Development Strategy (Country Studies, 2002)
Although many of the problems that Cali is experiencing - social and human capital deterioration, a declining economy, and institutional crisis - are a reflection of Colombia's complicated socioeconomic situation, the city has been hit harder by the crisis than other large cities, as confirmed by the following indicators: GDP, unemployment, poverty rate, inequality, and number of homicides. According to recent estimates, the population in Cali reached the 2 million level in 1999, making the city the second largest in the country after Bogota. Internal migration increased significantly during the early 90s due to the economic boom generated by drug dealing activities, and continued in the last part of the decade, due to resettlement movements of large population groups, affected by social conflict in rural areas. However, migration flows have generated social tension in the city, as economic opportunities became scarce. The Bank engaged in a participatory process to produce a City Development Strategy (CDS), whose specific objectives are to help the city administration and stakeholders identify a strategy to overcome the current crisis, and, be a neutral facilitator in the reconstruction process. The CDS is being developed in four stages: 1) identification of the main problems; 2) development of the analytical framework; 3) dissemination of results; and, 4) development of a financial plan